The effect of periodontal treatment in patients with atherosclerotic disease: Subject review (Revista Nacional de Odontología, 2018)
Introduction: Periodontal disease and atherosclerotic disease have high prevalence rates worldwide. Theyare also associated to chronic inflammatory response, in addition to presenting multiple risk factors in com-mon. Since it has been determined that periodontal treatment improves local inflammatory processes in thetooth’s supporting tissues and therefore aids local inflammatory response, a possible systemic impact hasbeen suggested in different illnesses such as, for example, cardiovascular diseases, arthritis and adverseeffects of pregnancy, among others. There is ample evidence that considers the presence of periodontaldisease in atherosclerotic diseases as an independent risk factor, but recent evidences from clinical studiesidentify the effects of periodontal treatment in specific cases. Purpose: To acknowledge existing relevant evidence about the effect of periodontal treatment in patientswith atherosclerotic disease between 2005 and 2016. Method: Research was conducted in English and Spanish in PubMed, Embase and Lilacs databases. Thekeywords employed were: “periodontal disease”, “periodontal diseases treatment”, “atherosclerosis”, “pe-riodontitis”, and “periodontal disease.” Results: Fourteen articles were found that showed a significant relationship in the effectiveness of perio-dontal treatment with plasma levels or inflammatory markers such as C-reactive protein and IL-6, amongothers, and a favorable response in endothelial function. The evidence found had a time-lapse greater thansix months after periodontal treatment. Conclusion: Results emphasize the effectiveness and urge of diagnosis and periodontal treatment in patientswith atherosclerosis, in order to reduce their risk factors.
Keywords: atherosclerosis; periodontal disease; periodontitis; periodontal treatment